Design and biological evaluation of tetrahydropyridine derivatives as novel human GPR119 agonists. Issue 4 (15th February 2020) - Zuo, Zeping; Chen, Miaomiao; Shao, Xiaoni; Qian, Xinying; Liu, Xiaocong; Zhou, Xia; Xiang, Jiawei; Deng, Pengchi; Li, Yan; Jie, Hui; Liu, Chunqi; Cen, Xiaobo; et al.
Graphical abstract: Abstract: A series of novel tetrahydropyridine derivatives were prepared and evaluated using cell-based measurements. Systematic optimization of general structure G-1 led to the identification of compound 35 (EC50 = 4.9 nM) and 37 (EC50 = 8.8 nM) with high GPR119 agonism activity and moderate clog P. Through single and long-term pharmacodynamic experiments, we found that compound 35 showed a hypoglycemic effect and may have an effect on improving basal metabolic rate in DIO mice. Both in vitro and in vivo tests indicated that compound 35 was a potential potent GPR119 agonist in allusion to T2DM treatment.